Moore’s proof, warrant transmission and skepticism - Dierig, Simon (Philosophia, 2022)
Two major arguments have been advanced for the claim that there is a transmission failure in G. E. Moore’s famous proof of an external world. The first argument, due to Crispin Wright, is based on an epistemological doctrine now known as “conservatism.” Proponents of the second argument, like Nicholas Silins, invoke probabilistic considerations, most important among them Bayes’ theorem. The aim of this essay is to defend Moore’s proof against these two arguments. It is shown, first, that Wright’s argument founders because one of its premises, viz, conservatism, invites skepticism and must therefore be rejected. Then the probabilistic argument is challenged, yet not because its formal part is dubious, but rather on the grounds that it incorporates as an implicit premise an unconvincing philosophical claim. Finally, the most promising objection to dogmatism - understood here as the negation of conservatism - is repudiated.
Published online: 07 October 2021
Gesehen am 23.11.2022